2011
DOI: 10.2337/dc10-2421
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin Improves Endothelium-Dependent Vasodilatation in Type 2 Diabetes

Abstract: OBJECTIVETo investigate whether the dipeptidyl peptidase-4 inhibitor vildagliptin improves endothelium-dependent vasodilatation in patients with type 2 diabetes.RESEARCH DESIGN AND METHODSSixteen subjects with type 2 diabetes (age 59.8 ± 6.8 years, BMI 29.1 ± 4.8 kg/m2, HbA1c 6.97 ± 0.61) on oral blood glucose–lowering treatment were included. Participants received vildagliptin 50 mg b.i.d. or acarbose 100 mg t.i.d. for four consecutive weeks in a randomized, double-blind, cross-over design. At the end of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 27 publications
3
86
1
2
Order By: Relevance
“…The clinical characteristics and the fasting serum DPP4 activity of total 44 T1DM patients included in this cross-sectional study are detailed described in Table 1 showing beneficial pleiotropic effect beyond glycaemic control for this class of drugs [14,20] and simultaneously growing body of evidence about increased serum DPP4 activity in T1DM patients [12,13], this cross-sectional study was designed primarily in order to elucidate the possible association of serum DPP4 activity and DR as most 7 frequent microvascular complication in diabetes [3,4]. Metabolic and anthropometric variables and fasting serum DPP4 activity were assessed in two groups of T1DM patients according to the DR prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical characteristics and the fasting serum DPP4 activity of total 44 T1DM patients included in this cross-sectional study are detailed described in Table 1 showing beneficial pleiotropic effect beyond glycaemic control for this class of drugs [14,20] and simultaneously growing body of evidence about increased serum DPP4 activity in T1DM patients [12,13], this cross-sectional study was designed primarily in order to elucidate the possible association of serum DPP4 activity and DR as most 7 frequent microvascular complication in diabetes [3,4]. Metabolic and anthropometric variables and fasting serum DPP4 activity were assessed in two groups of T1DM patients according to the DR prevalence.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with animal data showing that DPP-4 inhibitors reduce BP when given alone but not when coadministered with an ACE inhibitor. 1,6 Additionally, DPP-4 inhibition with vildagliptin 14 potentiates endothelium-dependent vasodilation in response to acetylcholine, whereas others have reported that sitagliptin and alogliptin attenuated endothelial function based on changes in flow-mediated vasodilation in patients with type 2 diabetes mellitus. 15 These vascular findings have been implicated as a potential mechanism for augmented sympathetic activity that could have played a role in the increase in HF hospitalizations in the SAVOR TIMI 53 trial.…”
Section: Discussionmentioning
confidence: 99%
“…Following a single subcutaneous injection of exenatide (a DPP4 inhibitor) in T2D patients, improved postprandial endothelial function was associated with decreased triglyceride but not glucose concentrations [187]. In a randomized cross-over trial, vildagliptin compared with acarbose improved ACh-stimulated FABF in T2D patients [189].…”
Section: Antiglycemic Agents and Insulin Sensitizersmentioning
confidence: 99%